IMPLEMENTASI INDUSTRI KREATIF PADA PEMBELAJARAN PRODUK KREATIF DAN KEWIRUSAHAAN PADA SEKOLAH MENENGAH KEJURUAN DI SURAKARTA - Mey Ester Marbun; Singgih Prastawa (CV. ADIBA AISHA AMIRA, 2024)
This research aims to explore how the creative industry is implemented in the subject of Creative Product and Entrepreneurship (PKK) in vocational high schools (SMK) and the benefits of the creative industry for SMK students. The study adopts a qualitative method with a phenomenological approach. The research subjects are teachers and students in vocational high schools in Surakarta. Data collection techniques include observation, interviews, questionnaires, and document analysis. The data is analyzed using Miles and Huberman's interactive analysis, and data validity is ensured through the triangulation of methods and sources. The findings of this research are as follows: 1) an overview of the creative industry in the subject of Creative Product and Entrepreneurship in SMK, and 2) an understanding of the benefits of the creative industry for SMK students. The research indicates that students are able to learn and comprehend the development of Creative Products and Entrepreneurship subjects when they actively participate in the lessons. It is also evident that entrepreneurship education requires genuine competence. It is hoped that the creative industry can be integrated into entrepreneurship education, and both SMK students and educators should understand and utilize the creative industry in the subject of Creative Products and Entrepreneurship (PKK).